Leadership, Work Culture, and Job Stress Effects on Employee Performance: A Quantitative Study: Kepemimpinan, Budaya Kerja, dan Dampak Stres Kerja terhadap Kinerja Karyawan: Studi Kuantitatif - Dewi Maftukhatul; Vera Firdaus (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to investigate the impact of leadership, work culture, and job stress on employee performance in a total sampling of 100 respondents from a private organization. The study employs a quantitative approach, utilizing a multiple linear regression analysis with SPSS 22. The findings reveal that leadership has a positive and significant influence on employee performance, as does work culture. However, job stress, while positively related, does not exhibit significant effects on employee performance. These results provide valuable insights for organizations seeking to enhance employee performance through effective leadership and fostering a positive work culture. Highlights: Leadership positively influences employee performance. Positive work culture is a significant factor in improving employee performance. Job stress, while relevant, lacks significant impact on employee performance. Keywords: Leadership, Work Culture, Job Stress, Employee Performance, Quantitative Study